Mining, time and protest: Dealing with waiting in German coal mine planning. Issue 1 (January 2019) - Müller, Katja
Highlights: Aligning local temporalities to climate change benefits mine opponents. De-synchronising temporalities is a meaningful strategy in conflicts around mining. Waiting can entail stages of being stuck and stages of brave perseverance. Mine planning includes time-related power, exercised through stages of waiting. Abstract: Three villages in East Germany have been in a stage of waiting for the Jänschwalde-Nord coal mine since 2007. Through opening the mine planning procedure, the mining company implied a nexus of coal-time, which local residents tried to disturb, but did not question as such. These politics of time generated several stages of waiting, which could only be dealt with more efficiently through de-synchronising the struggle and mine planning. The coal-time nexus was exchanged for a narrative of time relating to Energiewende and climate change, allowing for waiting to be anticipated as an act of endurance and perseverance. Attending and realigning mining temporalities allowed mine opponents to live through the stage of waiting.